MARKET TRANSPARENCY AND PERSONAL DATA PROTECTION IN CAPITAL MARKETS: RECONCILING DISCLOSURE AND PRIVACY - Michael H. Hadylaya (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
Capital markets depend on transparency to ensure fair pricing, investor protection, and market integrity, yet digitalization has expanded disclosure practices to include increasingly granular information that may identify individual investors or beneficial owners. This development creates tension between regulatory objectives of market transparency and the protection of personal data. This study examines how disclosure obligations in Indonesian capital market regulation interact with personal data protection law using a normative legal research approach based on statutory analysis and relevant literature. The findings indicate that the perceived conflict arises from the coexistence of two regulatory regimes pursuing distinct public interests: efficient markets and individual privacy. Existing legal provisions allow reconciliation by treating mandatory disclosure as lawful data processing grounded in statutory authority, provided that such disclosure remains proportionate and limited to information necessary for investor protection. The study concludes that effective governance in data-driven financial markets requires integrating transparency and privacy through calibrated disclosure practices rather than treating them as mutually exclusive objectives.